Nutrient constraints to tropical agroecosystem productivity in long-term degrading soils - Ngoze, S.; Riha, S.; Lehmann, Johannes; Kinyangi, James; Verchot, Louis V.; Mbugua, D.; Pell, A. (Wiley, 2008)
Soil degradation is one of the most serious threats to sustainable crop production in many tropical agroecosystems where extensification rather than intensification of agriculture has occurred. In the highlands of western Kenya, we investigated soil nitrogen (N) and phosphorus (P) constraints to maize productivity across a cultivation chronosequence in which land-use history ranged from recent conversion from primary forest to 100 years in continuous cropping. Nutrient treatments included a range of N and P fertilizer rates applied separately and in combination. Maize productivity without fertilizer was used as a proxy measure for indigenous soil fertility (ISF). Soil pools of mineral nitrogen, strongly bound P and plant-available P decreased by 82%, 31% and 36%, and P adsorption capacity increased by 51% after 100 years of continuous cultivation. For the long rainy season (LR), grain yield without fertilizer declined rapidly as cultivation age increased from 0 to 25 years and then gradually declined to a yield of 1.6 Mg ha−1, which was maintained as time under cultivation increased from 60 to 100 years. LR grain yield in the old conversions was only 24% of the average young conversion grain yield (6.4 Mg ha−1). Application of either N or P alone significantly increased grain yield in both the LR and short rainy (SR) seasons, but only application of 120 kg N ha−1 on the old conversion increased yield by >1 Mg ha−1. In both SR and LR, there was a greater average yield increment response to N and P when applied together (ranging from 1 to 3.8 Mg ha−1 for the LR), with the greatest responses on the old conversions. The benefit–cost ratio (BCR) for applying 120 kg N ha−1 alone was <1 except on the old conversions, while BCRs were>1 for applying 25 kg P ha−1 alone at all levels of conversion for both seasons. Application of both N (120 kg N ha−1) and P (25 kg P ha−1) on the old conversions resulted in the greatest BCRs. This study clearly indicates that maize productivity responses to N and P fertilizer are significantly affected by the age of cultivation and its influence on ISF, but that loss of productivity can be restored rapidly when these limiting nutrients are applied. Management strategies should consider ISF and economic factors to determine optimal N and P input requirements for achieving and sustaining profitable crop production on degraded soils.